The relationship between family-friendly work environment and intention to stay and the mediating effects of work-family factors - Noraani Mustapha (2011)
Problem statement: Employee loyalty has long been an issue in the field of human resource since it is related to behaviors such as attendance, turnover, organizational citizenship, lost of organizational memory and effectiveness. Approach: This study was conducted to test the mediating effects of work-family facilitation and family satisfaction on the relationship between family-friendly work environment as the independent variable and intention to stay as the dependent variable. By using self-administered research questionnaire, data was collected from 240 mid-age single mother employees in Klang Valley, Malaysia through simple random sampling method. Findings: The findings indicated that there were positive significant relationships among variables. The results also established the presence of mediation effects between the independent and dependent variables. Conclusion: Organizations may utilize family-friendly work factors along with work-family facilitation and family satisfaction as mechanisms to promote longer retention among employees